INCLUSIVE PI-0 PRODUCTION BY E+E- ANNIHILATION AT 34.6 GEV CENTER OF MASS-ENERGY - Braunschweig, W; Gerhards, R; Kirschfink, F; Martyn, H; Rosskamp, P; Vogel, E; Wallraff, W; Bock, B; Eisenmann, J; Fischer, H; Hartmann, H; Hilger, E; et al. (Springer-Verlag, 1986)
The cross section for the process e+e-→π0+ anything has been measured at an average center of mass energy of 34.6 GeV for π0 energies between 0.7 and 17 GeV. The angular distribution for π0 energies larger than 2 GeV is of the form dσ/dΩ∼1+Acos2θ, with A=1.2±0.5. The ratio of π0 to π± production in the measured energy range is 2σ(π0)/(σ(π+)+σ(π-))=1.13±0.18 The form of the differential cross sections agrees within the errors. The mean π0 multiplicity is 5.8±0.9. © 1986 Springer-Verlag.